Bias-induced instability in an intrinsic hydrogenated amorphous silicon layer for thin-film solar cells. (October 2016) - Lee, Youngseok; Park, Cheolmin; Park, Jinjoo; Oh, Donghyun; Lee, Youn-Jung; Yi, Junsin
Graphical abstract: Highlights: The mechanism for metastable defects creation was presented. The layer has the best durability against electrical bias stress was prepared. The results can be used for fabricate more stable a- Si:H thin film solar cell. Abstract: In this article we present a mechanism for creating metastable defects in intrinsic hydrogenated amorphous silicon (a-Si:H) layers by changing the flow-rate ratio of SiH4 and H2 . This is an important cardinal property that restricts the performance of both solar cells and thin-film transistors (TFT). Light or electrical bias results in generation of metastable dangling bonds. We evaluated the gas flow-rate ratio dependence of current decrease before and after application of electrical bias stress. Furthermore, we produced an a-Si:H TFT for comparison with a single-layer a-Si:H. Intrinsic layers deposited by SiH4 to H2 flow-rate ratios of 1:3 exhibited greater resistance to stress. In a-Si:H single layer experiment, we got a similar result, samples with SiH4 and H2 flow-rate ratios of 1:3 exhibited less decrease in current after application of electrical bias stress. These results will facilitate fabrication of more-stable a- Si:H thin film p-i-n solar cells.